2016
DOI: 10.1186/s12889-016-3560-5
|View full text |Cite|
|
Sign up to set email alerts
|

Health, disability and quality of life among trans people in Sweden–a web-based survey

Abstract: BackgroundSwedish research concerning the general health of trans people is scarce. Despite the diversity of the group, most Swedish research has focused on gender dysphoric people seeking medical help for their gender incongruence, or on outcomes after medical gender-confirming interventions. This paper examines self-rated health, self-reported disability and quality of life among a diverse group of trans people including trans feminine, trans masculine, and gender nonbinary people (identifying with a gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 47 publications
(50 reference statements)
1
34
0
3
Order By: Relevance
“…Also, previous studies observed the importance of preoperative expectations of surgery and experienced complications on quality of life after gender-confirming operations. 11 , 12 As mastectomies are frequently followed by secondary corrections, surgeons should prepare trans men to anticipate possible disappointing outcomes after initial surgery and the possible need for revision surgery. Patient-reported outcomes after mastectomy were related to co-occurring depressive symptoms, assessed by the screening question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, previous studies observed the importance of preoperative expectations of surgery and experienced complications on quality of life after gender-confirming operations. 11 , 12 As mastectomies are frequently followed by secondary corrections, surgeons should prepare trans men to anticipate possible disappointing outcomes after initial surgery and the possible need for revision surgery. Patient-reported outcomes after mastectomy were related to co-occurring depressive symptoms, assessed by the screening question.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Past studies of the effectiveness of mastectomy found that body image improved after surgery, 8 , 9 as did psychological well-being and experienced gender dysphoria. 10 Factors associated with treatment satisfaction and quality of life included treatment expectations, 11 physical appearance, 9 health care experiences and complications, 11 , 12 psychological distress, 9 and social support and discrimination. 13 …”
mentioning
confidence: 99%
“…In the publication of this article [ 1 ] it was brought to our attention that the last sentence on page 12 incorrectly states: “Legal gender recognition, in the context of this study, is a precondition for access to gender-confirming health care”. The correct sentence should read: “Gender-confirming health care, in the context of this study, is a precondition for access to legal gender recognition”.…”
Section: Erratummentioning
confidence: 99%
“…After screening and removing incomplete and noneligible responses, 796 respondents remained for the analysis. 22 …”
Section: Methodsmentioning
confidence: 99%
“…The categorization was carried out in a structured way according to specific requirements, which are described in detail elsewhere. 22 …”
Section: Methodsmentioning
confidence: 99%